A high-speed and long-life triboelectric sensor with charge supplement for monitoring the speed and skidding of rolling bearing. (February 2022) - Xie, Zhijie; Wang, Yu; Wu, Rensuan; Yin, Jihui; Yu, Di; Liu, Jiuqing; Cheng, Tinghai
Abstract: Rolling bearing is the core component of rotating machinery and its operation status greatly affects the stability of equipment. In this paper, a non-contact triboelectric bearing sensor (NC-TEBS) was proposed for monitoring the speed and skidding of rolling bearing. The NC-TEBS adopts the coupling electrode structure of non-contact induction and sweeping. It is composed of PTFE ring, grid electrode, and sweeping charge supplement device. The charge supplement device can increase the surface charge density and ensure the strength of the output signal. When the bearing runs, the PTFE ring rotates with the cage and moves relative to the grid electrode, generating periodic electrical signals via electrostatic induction. The bearing speed can be monitored in low-speed conditions, while the bearing skidding rate can be monitored in high-speed and light-load conditions. The experimental results have shown that the NC-TEBS has an ultra-wide working speed range of 10–5000 rpm. Its maximum working speed is more than twice that of the reported triboelectric speed sensor. The maximum NC-TEBS error value regarding the detection speed is less than 1.8 rpm, with the maximum error rate below 0.25%. After 5 000 000 revolutions under continuous operation, the open-circuit voltage amplitude did not decay, indicating that NC-TEBS has an ultra-long service life. Finally, the NC-TEBS developed in this paper can monitor the operation status of rolling bearing in real-time, with the characteristics of miniaturization and integration. As such, it provides a theoretical and experimental basis for the development of new self-driven and self-sensing smart bearings. Graphical Abstract: ga1 Highlights: A non-contact triboelectric bearing sensor (NC-TEBS) was proposed for monitoring the speed and skidding rate of bearing. The NC-TEBS has an ultra-wide working speed range, and its maximum speed can reach 5000 rpm. The NC-TEBS has an ultra-long service life with no decay of output signal voltage amplitude after 5 000 000 revolutions. The NC-TEBS can monitor bearing operation status in real-time, providing the basis for development of new smart bearings.